Di-tert-butyl 2,2 `-[(biphenyl-4,4 `-diyl)dioxy]diacetate - Ali, Q.; Yousuf, S.; Shah, M.R.; Ng, S.W. (International Union of Crystallography, 2010)
The complete molecule of the title compound, C(24)H(30)O(6), is generated by a crystallographic inversion centre. In the unique part of the molecule, the four-atom -O-CH(2)-C(O)-O-chain between the benzene ring and the tert-butyl group assumes a zigzag conformation [O-C-C-O torsion angle = -162.3 (1)degrees].